The role of leadership style in increasing work productivity among teachers and staff at SD Negeri 3 Getasrejo, Grobogan Regency - Farah Anisa Isnaini; Dita Prameswari (LPPM Universitas An Nuur, 2025)
Background & Purpose: In an organization, Human Resources management is a series of organizational activities directed at attracting, developing and retaining an effective workforce. If Human Resource Management uses good concepts, it will also have an influence on the running of an organization. Likewise, if the Human Resources management concept is not good, it will have a negative impact on the organization. According to Ajabar (2020) Human Resource Management is an activity that is attempted to trigger, improve, motivate and maintain good performance in the organization. HR are humans who are employed in an agency as movers, thinkers and planners to achieve organizational goals (Sulistyowati, 2021). Human Resources According to Edison Emron, et al (2020) is management that focuses on maximizing the abilities of its employees or members through various strategic steps in order to improve employee or employee performance towards optimizing organizational goals Education in Indonesia plays a very important role in nation development, especially human resource development. Education always experiences changes, developments and improvements in accordance with developments in all areas of life. Educational productivity in schools can be seen from outstanding educational output and the educational process in the form of an educational atmosphere. Education plays a very important role in increasing national productivity by producing quality human resources (HR). Productivity is important to make an organization or individual more efficient, effective and of high quality.Method: The number of samples in this study was 8 people within 1 month consisting of 5 teachers and 3 staff at SD Negeri 3 Getasrejo, Grobogan Regency.Results: The role of leadership style applied by the principal of SD Negeri 3 Getasrejo starting from wisdom, responsibility, decision making, solving problems and motivation for 8 predetermined sources. In the role of leadership style, there are 2 stages of the role to increase the resulting productivity, namely the first stage through the principal's approach, guiding and communicating effectively, maintaining loyalty, decision making, solving problems, and the type of leadership that must be applied by the principal at this time.Conclusion & Suggestion: Leadership can be identified by approaching superiors and subordinates through wisdom, communicating effectively, maintaining loyalty, being responsible, decision making processes, and providing motivation and there are several factors to increase work productivity, namely there is motivation from superiors to subordinates, responsibility in completing work, enjoying work, and being able to explore the potential of subordinates and there are 3 ideal typical leadership styles